2013
DOI: 10.4161/epi.27323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of folic acid fortification on global DNA methylation and one-carbon biomarkers in the Women's Health Initiative Observational Study cohort

Abstract: DNA methylation is an epigenetic mechanism that regulates gene expression and can be modified by one-carbon nutrients. The objective of this study was to investigate the impact of folic acid (FA) fortification of the US food supply on leukocyte global DNA methylation and the relationship between DNA methylation, red blood cell (RBC) folate, and other one-carbon biomarkers among postmenopausal women enrolled in the Women's Health Initiative Observational Study. We selected 408 women from the highest and lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
(56 reference statements)
0
28
1
Order By: Relevance
“…First, the recruitment for the Women's Health Initiative Observational Study spanned periods before (1994‐1995), during (1996‐1997), and after (1998) nationally mandatory folic acid fortification, which led to an upshift in folate status . Thus, the expression of FOCM genes and their influences on CRC risks might have been modified in the era of folic acid fortification . Second, a certain number of false‐positive results might have occurred when we investigated the gene‐nutrient interactions even though we implemented several measures to minimize this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…First, the recruitment for the Women's Health Initiative Observational Study spanned periods before (1994‐1995), during (1996‐1997), and after (1998) nationally mandatory folic acid fortification, which led to an upshift in folate status . Thus, the expression of FOCM genes and their influences on CRC risks might have been modified in the era of folic acid fortification . Second, a certain number of false‐positive results might have occurred when we investigated the gene‐nutrient interactions even though we implemented several measures to minimize this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Age and sex were included since they are commonly known to influence gene methylation. Folate level was included as different levels of folate status could confound the ability to produce methyl donors [33] and WHR was included as this has been identified as a strong factor that influences insulin resistance in SGA users [17] . A statistically significant result was set at p < 0.05 and analyses were ran using R version 3.1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies reported a statistically significant positive correlation between higher blood folate levels and higher LINE-1 levels [37, 52]. However, in one of the same studies, folate intake from natural foods and total dietary folate equivalents were not found to be associated with higher LINE-1 levels [37].…”
Section: Resultsmentioning
confidence: 99%